Análise do comportamento ético corporativo, evidenciado por meio de indicadores constantes do balanço social - Käfer, Neuza Cristina Caeppel (2015)
This paper had as its goal the identification of the perception of the workers of the Esmeralda Company with regard to ethical actions and conducts based on Christian principles, published in the Social Report. The study is justified since the publication of this report of social activities is still not obligatory, which brings up the need to verify in a scientific way if the information divulged in a spontaneous way is also known to the stakeholders. This is a case study, with a quantitative approach using a survey on the Likert scale. The social indicators which the company makes public through the divulgement of the Social Report in the Legislative Assembly of the State of Mato Grosso site were analyzed. The paper is structured in seven chapters, being divided into: introductory considerations, conceptual base about ethical thinking, literary review about Business Social Responsibility, Social Report, methodology, analysis of the data and final considerations about the perception of the collaborators of the Esmeralda Company with regard to the social actions divulged in the Social Report. It is difficult to talk of ethics in current times without relating it to the collective. It is ethics that marks the existence, the relations, so that the concept of ethics cannot be explained in an individual manner, since, even if living isolated, at some moment in Iife it is necessary to establish relations and isolation is one way to not agree with what is happening in current societies. Value is the total respect for all the ethical principles and therefore, for the company to define its values, it also needs to know what is useful for it and what is essential for it to subsist, maintaining a healthy environment providing the capacity for growth of its collaborators. According to KROETZ (2000), the Social Report is a complementary report of the accounting statements and aims at explaining the impacts resulting from the company activity, as well as demonstrating the capacity of the openness of the company to dialog and of the efforts made to attend to the legitimate interests of the interested parts. The analysis of the perception of the workers of the Esmeralda Company with respect to the ethical actions and conducts guided by Christian principles, based on the indicators of the Social Report was developed in four distinct topics from the perspective of: the Data of Identification and Presentation of the Respondents, Social Indicators, Workforce and the Exercise of Business Citizenship. It was observed that, in a general way, the stakeholders perceive an ethical relation in the social actions published in the Social Report of the Esmeralda Company and that they are in agreement with the values and beliefs of the organization, demonstrating its social responsibility toward the community in which it is inserted.